Clinical efficacy of polymer-based paclitaxel-eluting stents in the treatment of complex, long coronary artery lesions from a multicenter, randomized trial: support for the use of drug-eluting stents in contemporary clinical practice. - Dawkins, K; Grube, E; Guagliumi, G; Banning, A; Zmudka, K; Colombo, A; Thuesen, L; Hauptman, K; Marco, J; Wijns, W; Popma, J; Koglin, J; et al. (2005)
BACKGROUND: Intracoronary polymer-based stent delivery of paclitaxel has been shown to be effective in reducing restenosis in simple coronary lesions, but the evidence base for contemporary use in longer, more complex coronary stenoses is lacking. METHODS AND RESULTS: TAXUS VI is a prospective, multicenter, double-blind, randomized trial assessing clinical and angiographic outcomes of the TAXUS Moderate Release paclitaxel-eluting stent in the treatment of long, complex coronary artery lesions. Four hundred forty-eight patients at 44 sites were randomized (1:1) between a drug-eluting TAXUS Express2 and an uncoated Express2 control stent. Per protocol, the 9-month follow-up included an angiographic reevaluation in all patients. The primary end point was the rate of target-vessel revascularization 9 months after the study procedure; secondary end points included the rate of target-lesion revascularization and binary restenosis at follow-up. Mean lesion length in the study was 20.6 mm, with a mean stent-covered length of 33.4 mm. Of all lesions, 55.6% were classified as complex lesions (type C of the AHA/ACC classification). At 9 months, target-vessel revascularization was 9.1% in the TAXUS group and 19.4% in the control group (P=0.0027; relative reduction, 53%). Target-lesion revascularization was reduced from 18.9% to 6.8%, respectively (P=0.0001). The incidence of major adverse cardiac events was similar in the 2 groups, 16.4% and 22.5% in TAXUS and control, respectively (P=0.12), including comparable rates for acute myocardial infarction. Binary restenosis in the stented area was reduced from 32.9% in the control group to 9.1% in the TAXUS patients (P<0.0001). CONCLUSIONS: The finding that the TAXUS Moderate Release stent system is safe and effective in the treatment of long, complex coronary artery lesions provides the evidence base for the more widespread use of drug-eluting stents in contemporary clinical practice.